Agile project management and emerging technologies in concurrent engineering for sustainable and collaborative product design - Anyaora, Sunday Chimezie; Chukwumuanya, Emmanuel Okechukwu; Dara, Jude Ezechi; Ofochebe, Sunday Madubueze; Okoye, Chibuzo Ndubuisi (AGUSPATI Research Institute, 2025)
Designing sustainable and innovative products today requires more than just good ideas as it demands speed, flexibility, teamwork, and smart use of technology. This study used a systematic review approach guided by PRISMA to examine how Agile project management and emerging technologies enhance concurrent engineering for sustainable and collaborative product design. Literature was sourced from five major databases using targeted search terms. After a rigorous three-phase screening and quality appraisal, relevant studies were thematically synthesized around Agile, AI, automation, cloud platforms, ethics, circular economy, and composite manufacturing. The result showed that revealed that integrating Agile project management into concurrent engineering enhances flexibility, collaboration, and design responsiveness. Design automation and AI tools improve accuracy and decision-making, while cloud-based platforms strengthen real-time teamwork. Generative design supports creativity and rapid iteration. Ethical concerns like transparency and inclusivity emerged as essential. Circular economy strategies help reduce waste and extend product life. In composite manufacturing, concurrent engineering and group design improve material efficiency, product quality, and speed, demonstrating strong potential for sustainable innovation. The findings suggest that integrating Agile practices with emerging technologies creates a powerful framework for building smarter, greener, and more collaborative products now and in the future.